GENERATIVE ART AS PEDAGOGICAL TOOL IN ART SCHOOLS - Morales, Michelle; Morales Jr, Severino; Nayak, Dinesh Kumar; Mang, Purva; Sahu, Abhinesh Kumar; Sripada, Pushpa Nagini (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Generative art has become a paradigm shift in the modern art education industry where it provides a fresh way to explore creativity by means of algorithms and human-artificial intelligence. The paper discusses generative art as a pedagogical approach in art schools, highlighting its significance in transforming an outcome-oriented production instructional approach in favor of a process-based and reflective pedagogical approach of learning. It is suggested to implement a more systematic pedagogical model that incorporates methods of generative work into the studio-based curriculum by means of progressive course design, inquiry-based exploration, and human-AI design approaches to work. The paper also presents a curriculum- mapping scheme and process-based framework of assessment that anticipates the advancement of foreground iteration, conceptual articulation and reflective practice as the major indicators of creative development. The paper based on rubric based evaluation and illustrative visualization of analysis shows that learning outcomes in generative art education can be evaluated longitudinally, not using single points in form of artifacts. The results substantiate that the generative art improves the systems thinking, metacognitive awareness, and creative accountability as well as promotes the inclusive engagement of various learner profiles. The paper ends by pinpointing future directions of research that seeks to empirically validate and/or culturally responsive AI-assisted studio design, and sustainable AI-assisted studio processes, making generative art a central pedagogical initiative in the teaching of art to next-generation students.